2x(4x - 3) - (2x + 1)
=8x² - 6x - 2x - 1
= 8x² - 8x - 1
2007-01-12 05:00:29
·
answer #1
·
answered by Tom :: Athier than Thou 6
·
1⤊
0⤋
You have to remember to multiply each item in the parentheses:
2x ( 4x - 3) - (2x + 1) becomes:
8x*2 - 6x - 2x - 1 (don't forget to change the sign on the 1)
Simplifying:
8x*2 - 8x - 1
To solve for x, factor and set x = to zero:
2007-01-12 05:29:54
·
answer #2
·
answered by nammy_410 2
·
0⤊
0⤋
Resolve each term first:
8x^2 - 6x - 2x - 1
Add:
8x^2 -8x - 1 is the answer
2007-01-12 05:04:28
·
answer #3
·
answered by Nightstalker1967 4
·
1⤊
0⤋
10x+5 -3x+12 =7x+17 <---answer u do (5 circumstances 2x =10x) +(5 circumstances a million =5) minus.....(unfavorable 3 circumstances x = -3x and unfavorable 3 circumstances unfavorable 4 equals +12) then u upload each and each of the x's jointly ( so its 10x +(-3x) =7x and 5+12= 17) there fore ur answer is 7x+17
2016-10-30 22:22:49
·
answer #4
·
answered by ? 4
·
0⤊
0⤋
(8x^2-6x)-(2x+1)
The answer after subtracting would be: 8x^2-8x-1
2007-01-12 05:39:15
·
answer #5
·
answered by TJ 2
·
0⤊
0⤋
2x(4x - 3) - (2x + 1)
8x² - 6x - 2x - 1
8x² - 8x - 1
- - - - - - - s-
2007-01-12 05:41:16
·
answer #6
·
answered by SAMUEL D 7
·
0⤊
0⤋
2x(4x-3)-(2x+1)=
2*4*x*x-2*x*3-2x-1=
8x^2-6x-2x-1=
8x^2-8x-1
2007-01-12 05:19:32
·
answer #7
·
answered by Bill 1
·
0⤊
0⤋
8x-3-2x+1
=6x-2
2007-01-12 05:00:51
·
answer #8
·
answered by Sammy T 2
·
0⤊
4⤋
2x(4x-3)-(2x+1)
8x^2-6x-2x-1
8x^2-8x-1
2007-01-12 15:03:08
·
answer #9
·
answered by music_gurl62091 2
·
0⤊
0⤋
(8x^2 - 6x) - (2x +1)
2007-01-12 04:59:49
·
answer #10
·
answered by RobRetz 2
·
0⤊
2⤋